PENGARUH BRAND IMAGE TERHADAP LOYALITAS YANG DIMEDIASI BRAND TRUST PADA PENGGUNA SMARTPHONE - INDRA KURNIAWAN (Jurnal Akademika, 2016)
This study aims to determine the effect of brand loyalty mediated image of thebrand trust on a Samsung smartphone users in Jombang in 2015. The populationwas taken from Samsung Smartphone users who are in the Jombang district,using multistage sampling, involving 150 respondents. The analysis techniqueused in this study using Multiple Mediation which to measure and verify whetherbrand trust becomes the mediation of the effect of brand image to loyalty, as well asto measure the causal step of each construct. The results showed that the variableTrust (Trust) effect on the Loyalty variable. Brand Image variables also affectLoyalty variable. While the test results variable trust (Trust) is not proven as amediating variable of the influence of the brand image of the Loyalty.Keywords: brand image, loyalty, trust, influence, smatphone, Samsung